Control interno de inventarios del agrícola briones barragán s.a. En el periodo 2020. - Habate Real, Claudia Melania (2022)
The research project justifies its development since when carrying out an analysis of the internal control processes with which inventories are specifically managed. In addition, these factors affect the decrease in business profitability, on the other hand, non-compliance with the different regulations is caused by not having the allowed amount of inventory. The objective of this research is to analyze the internal inventory control of Agrícola Briones Barragán S.A. in the period 2020. The purpose of this case study is to analyze the "Internal inventory control of Agrícola Briones Barragán S.A. in the period 2020" located in the province of Los Ríos, Cantón Ventanas, with the objective of describing the problems that arise in the management of the merchandise used for the commercialization of the company. Considering that maintaining a good control of the inventory depends on the administration, it will be checked if they efficiently control the merchandise to obtain the necessary stock and meet the demand. Internal controls can be thought of as checks and balances to prevent errors and losses in various areas of a company.